Pharmacogenomic profiling and clarification of the role of the mismatch repair genes in response to the chemotherapeutic agent 5-Fluorouracil in a South African colorectal cancer cohort - Meyer, Jacqueline (Division of Human Genetics, 2014)
Includes abstract.